Capturing the barriers and strategic solutions for women empowerment: Delphy analytical network process - Widiastuti, Tika; Al-shami, Samer Ali; Mawardi, Imron; Zulaikha, Siti; Haron, Razali; Kasri, Rahmatina Awaliyah; Al Mustofa, Muhammad Ubaidillah; Puspa Dewi, Eka (Elsevier, 2024)
Even though Indonesia faces significant gender disparities across various sectors, including education, health, employment, and political representation, there remains a dearth of research addressing the barriers and strategic solutions for women’s empowerment, which is the aim of this study. A quantitative method driven by the Modified Penta Helix Model (MPM) and the Delphi Analytical Network Process (DANP) was used. On the one hand, MPM was used to establish renewal between the five strategic dimensions and other additional elements such as economic, socio-cultural, and education and training. On the other hand, D-ANP developed indicators based on Focus Group Discussions (FGD) outcomes, in-depth interviews, and structured questionnaires. According to this study, education and training are essential in empowering women. The results of this study indicate the main problems in empowering women, which are divided into eight main dimensions: economic, socio-cultural, education and training, government support, association support, academic support, media support, and private sector support. Education and training were the most critical problems in empowering women. Collaboration between academics, business, community, government, and media is essential to develop effective education and training programs to empower women in Indonesia. Through employing D-ANP and MPM methodologies, this study suggests a model of women’s economic empowerment to improve the quality of Indonesian women and Indonesia’s position in the Women’s Empowerment Index.